VLT-SINFONI sub-kpc study of the star formation in local LIRGs and ULIRGs Analysis of the global ΣSFR structure and characterisation of individual star-forming clumps - Piqueras López, J; Colina, L; Arribas, S; Pereira-Santaella, M; Alonso-Herrero, A (EDP Sciences, 2016)
We present a two-dimensional study of star formation at kiloparsec and sub-kiloparsec scales of a sample of local (z < 0.1) luminous (10) and ultraluminous (7) infrared galaxies (U/LIRGs), based on near-infrared VLT-SINFONI integral field spectroscopy (IFS). We obtained integrated measurements of the star formation rate and star formation rate surface density, together with their 2D distributions, based on Brγ and Paα emission. In agreement with previous studies, we observe a tight linear correlation between the star formation rate (SFR) derived from our extinction-corrected Paα measurements and that derived from Spitzer 24 μm data, and a reasonable agreement with SFR derived from LIR. We also compared our SFRPaα values with optical measurements from Hα emission and find that the SFRPaα is on average a factor ~3 larger than the SFRHα, even when the extinction corrections are applied. Within the angular resolution and sizes sampled by the SINFONI observations, we found that LIRGs have a median-observed star formation rate surface density of ΣLIRGsobs=1.16 M⊙ yr-1 kpc-2, and ΣLIRGscorr=1.72  M⊙ yr-1 kpc-2 for the extinction-corrected distribution. The median-observed and the extinction-corrected ΣSFR values for ULIRGs are ΣULIRGsobs=0.16  M⊙ yr-1 kpc-2 and ΣULIRGscorr=0.23  M⊙ yr-1 kpc-2, respectively. These median values for ULIRGs increase up to 1.38 M⊙ yr-1 kpc-2 and 2.90 M⊙ yr-1 kpc-2, when only their inner regions, covering the same size as the average FoV of LIRGs, are considered. For a given fixed angular sampling, our simulations show that the predicted median of the ΣSFR distribution increases artificially with distance, a factor ~2–3 when the original measurements for LIRGs are simulated at the average distance of our ULIRGs. This could have consequences on any estimates of the star formation surface brightness in high-z galaxies, and consequently on the derivation of the universality of star formation laws at all redshifts. We identified a total of 95 individual star-forming clumps in our sample of U/LIRGs, with sizes that range within ~60–400 pc and ~300–1500 pc, and extinction-corrected Paα luminosities of ~105–107 L⊙ and ~106–108 L⊙ in LIRGs and ULIRGs, respectively. The ΣSFR of the clumps presents a wide range of values within 1–90 M⊙ yr-1 kpc-2 and 0.1–100 M⊙ yr-1 kpc-2 for LIRGs and ULIRGs. Star-forming clumps in LIRGs are about ten times larger and thousands of times more luminous than typical clumps in spiral galaxies, which is consistent with expected photon-bounded conditions in ionized nebulae that surround young stellar clusters. Clumps in ULIRGs have sizes similar (×0.5–1) to those of high-z clumps, having Paα luminosities similar to some high-z clumps, and about 10 times less luminous than the most luminous high-z clumps identified so far. This could be an indication that the most luminous giant clumps in high-z star-forming galaxies are forming stars with a higher surface density rate than low-z compact ULIRGs. We also observed a change in the slope of the L-r relation, from η = 3.04 of local samples to η = 1.88 from high-z observations. A likely explanation is that most luminous galaxies are interacting and merging, and therefore their size represents a combination of the distribution of the star-forming clumps within each galaxy in the system plus the additional effect of the projected distance between the galaxies. As a consequence, this produces an overall size that is larger than that of individual clumps, or galaxies (for integrated measurements)